Beyond the Surface: Why Community Health Nurses Should Embrace the Critical Realist Perspective - Rahman, Framita (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Researchers have often reflected on why improving community health remains a persistent challenge, and why many well-intentioned policies and interventions are often difficult to sustain or fall short in addressing complex health issues. Through the PhD journey at the University of Edinburgh, the researcher developed a deeper understanding of how community health nurses’ practice is shaped by social, cultural, and structural dynamics. This journey has also highlighted the importance of addressing the social determinants of health and adopting a critical realist lens to explore not only what happens in communities but also why, for whom, and under what conditions. This approach offers a stronger foundation for the design of effective and sustainable interventions.